The Benefits of Cognitive Behavior Therapy in Persistent Postural-Paroxysmal Dizziness: O Benefício da Terapia Cognitivo-Comportamental na Tontura Persistente Postural-Paroxística - Neves, José; Machado, Sara; Castro, José Luís; Barreira, Pedro; Sanches, Raquel (Gazeta Médica, 2019)
INTRODUCTION: Persistent postural-paroxysmal dizziness is a recently recognized entity, affecting about 10% of the patients complaining with dizziness. Its treatment involves pharmacological therapy with selective serotonin reuptake inhibitors, associated or not with a vestibular rehabilitation program. Given the difficult management of these patients and resistance to conventional treatment, cognitive behavioral therapy appears as a treatment possibility for this condition. The objective of this study is to determine if there is benefit in using cognitive behavioral therapy in the treatment of persistent postural-paroxysmal dizziness. METHODOLOGY: A search was performed using the keywords “persistent postural perceptual dizziness”, “cognitive behavioral therapy”, “phobic postural vertigo” in the following databases: National Guideline Clearinghouse, Canadian Medical Association Practice Guidelines InfoBase, DARE - Database of abstracts of reviews of effectiveness, Evidence-Based Medicine and PubMed. Other articles mentioned in the initial research were also included. RESULTS: Three articles were identified in the databases. Two additional articles mentioned in the initial research were included. In total five articles were included: two case-control studies and three literature reviews. DISCUSSION: The benefit of cognitive behavioral therapy as part of a multidisciplinary approach is consensual. Improvements in dizziness, anxiety and depression have been reported in these patients. There was also improvement in postural control and decrease in the medication dosages required. The long-term effects of cognitive behavioral therapy are still inconsistent. CONCLUSION: Cognitive behavioral therapy seems to be a valid therapeutic option in association with other measures. We stress the lack of scientific evidence in this area and the need for further studies.